Differing natural killer cell, T cell and antibody profiles in antiretroviral-naive HIV-1 viraemic controllers with and without protective HLA alleles. - Ana Moyano; Bongiwe Ndlovu; Msizi Mbele; Kewreshini Naidoo; Nasreen Khan; Jaclyn K Mann; Thumbi Ndung'u (PLoS ONE, 2023)
Previous work suggests that HIV controllers with protective human leukocyte antigen class I alleles (VC+) possess a high breadth of Gag-specific CD8+ T cell responses, while controllers without protective alleles (VC-) have a different unknown mechanism of control. We aimed to gain further insight into potential mechanisms of control in VC+ and VC-. We studied 15 VC+, 12 VC- and 4 healthy uninfected individuals (UI). CD8+ T cell responses were measured by ELISpot. Flow cytometry was performed to analyse surface markers for activation, maturation, and exhaustion on natural killer (NK) cell and T cells, as well as cytokine secretion from stimulated NK cells. We measured plasma neutralization activity against a panel of 18 Env-pseudotyped viruses using the TZM-bl neutralization assay. We found no significant differences in the magnitude and breadth of CD8+ T cell responses between VC+ and VC-. However, NK cells from VC- had higher levels of activation markers (HLA-DR and CD38) (p = 0.03), and lower cytokine expression (MIP-1β and TNF-α) (p = 0.05 and p = 0.04, respectively) than NK cells from VC+. T cells from VC- had higher levels of activation (CD38 and HLA-DR co-expression) (p = 0.05), as well as a trend towards higher expression of the terminal differentiation marker CD57 (p = 0.09) when compared to VC+. There was no difference in overall neutralization breadth between VC+ and VC- groups, although there was a trend for higher neutralization potency in the VC- group (p = 0.09). Altogether, these results suggest that VC- have a more activated NK cell profile with lower cytokine expression, and a more terminally differentiated and activated T cell profile than VC+. VC- also showed a trend of more potent neutralizing antibody responses that may enhance viral clearance. Further studies are required to understand how these NK, T cell and antibody profiles may contribute to differing mechanisms of control in VC+ and VC-.